Characterization of AQX‐1125, a small‐molecule SHIP1 activator. (25th February 2013) - Stenton, Grant R; Mackenzie, Patrick Tam, Lloyd F; Cross, Jennifer L; Harwig, Curtis; Raymond, Jeffrey; Toews, Judy; Wu, Joyce; Ogden, Nancy; MacRury, Thomas; Szabo, Csaba
<x xml:space="preserve">Abstract</x> Background The SH2‐containing inositol‐5′‐phosphatase 1 (SHIP1) metabolizes PI(3, 4, 5)P3 to PI(3, 4)P2. SHIP1‐deficient mice exhibit progressive inflammation. Pharmacological activation of SHIP1 is emerging as a potential therapy for pulmonary inflammatory diseases. Here we characterize the efficacy of AQX‐1125, a small‐molecule SHIP1 activator currently in clinical development. Experimental Approach The effects of AQX‐1125 were tested in several in vitro assays: on enzyme catalytic activity utilizing recombinant human SHIP1, on Akt phosphorylation in SHIP1‐proficient and SHIP1‐deficient cell lines, on cytokine release in murine splenocytes, on human leukocyte chemotaxis using modified Boyden chambers and on β‐hexosaminidase release from murine mast cells. In addition, pharmacokinetic and drug distribution studies were performed in rats and dogs. Results AQX‐1125 increased the catalytic activity of human recombinant SHIP1, an effect, which was absent after deletion of the C2 region. AQX‐1125 inhibited Akt phosphorylation in SHIP1‐proficient but not in SHIP1‐deficient cells, reduced cytokine production in splenocytes, inhibited the activation of mast cells and inhibited human leukocyte chemotaxis. In vivo, AQX‐1125 exhibited >80% oral bioavailability and >5 h terminal half‐life. Conclusions Consistent with the role of SHIP1 in cell activation and chemotaxis, the SHIP1 activator AQX‐1125 inhibits Akt phosphorylation, inflammatory mediator production and leukocyte chemotaxis in vitro. The in vitro effects and the pharmacokinetic properties of the compound make it a suitable candidate for in vivo testing in various models of inflammation. Linked Article This article is accompanied by Stenton et al., pp. 1519–1529 of this issue. To view this article visit http://dx.doi.org/10.1111/bph.12038